Public Facilities in the City of Semarang from the Elderly Perception - Sri Sumijati; Suparmi Suparmi (Universitas Katolik Soegijapranata, 2020)
The purpose of this study was to determine the perception of the elderly about public facilities in Semarang on four aspects, namely public buildings, hospitals, roadways and public transportations. Forty eight elderly range from 60 to 90 years old agree to become our respondents. Data collected by structured interview and analized quantitatively as well as qualitatively. In general this research shown that no contrast difference between positive and negative perception. Data analysis found that (1) the hospital was perceived to be the most positive, followed by public buildings, public transportations and roadways, (2) most of the subjects perceived the hospital’s facilities were quite good, where information service was the best sub-aspects, (3) in related to public transportation the city buses are better than angkot. We suggest to the government to make Semarang a friendly city for the elderly, especially in improving the pavement and trans bus stops, public transportation driver behavior, and making it easier to register online at hospitals.